TNI is Not an Office Guard, But a Guard of the Future of the Country Review of The Policy of Army Guarding the Prose-cutor's Office - A. Junaedi Karso (International Forum of Researchers and Lecturers, 2025)
Deployment of TNI to secure the prosecutor's office Although the Policy arose based on Telegram No. TR/442/2025 which ordered the deployment of TNI soldiers to strengthen the security of the High Prosecutor's Office and the District Prosecutor's Office throughout Indonesia.Securing the prosecutor's office by the TNI is contrary to civilian supremacy, a distortion of the defense function, because it deviates from the spirit of reform and the constitution. Meaning When the law is passed by legal telegram, the deployment of the military for tasks other than war or what is known as Military Operations Other Than War (OMSP), is strictly regulated in Law Number 3 of 2025 concerning Amendments to Law No. 34 of 2004 concerning the TNI. In Article 7 paragraphs (3) and (4), it is emphasized that: (1). All forms of OMSP can only be carried out based on a state political decision, either in the form of a Presidential Regulation or Government Regulation, depending on the type and scope of its duties. This is a form of